Total Synthesis and Structure Confirmation of (−)-Asimitrin, a C37 Annonaceous Acetogenin with a Hydroxylated Adjacent Bis-Tetrahydrofuran Core - Kwak, Soo Yeon; Park, Youngjik; Lim, Seongju; Jang, Hongjun; Lee, Dongjoo; Kim, Hyoungsu; Kim, Deukjoon (Organic Letters, 2023)
The total synthesis and structure confirmation of the potent cytotoxic agent (−)-asimitrin (1), a C37 annonaceous acetogenin having a hydroxylated adjacent bis-tetrahydrofuran (THF) core, are described. The present synthesis features a highly stereoselective, chelate-controlled intramolecular amide enolate alkylation (IAEA) for the synthesis of key intermediate 17-hydroxy-16,17-erythro-16,19-trans-THF 6, our direct ketone synthesis/l-Selectride reduction protocol for stereoselective introduction of the C(21)-C(34) unit, Sharpless asymmetric dihydroxylation (SAD), and internal Williamson etherification for construction of the 20,23-trans-THF ring.